Evaluation of Metachronous Breast and Endometrial Cancers: Preroutine and Postroutine Adjuvant Tamoxifen Use. Issue 8 (1st October 2016) - Grzankowski, Kassondra S.; Szender, J. Brian; Spring-Robinson, Chandra L.; Lele, Shashikant B.; Odunsi, Kunle O.; Frederick, Peter J.
Abstract : Background: The time interval between diagnoses of breast cancer (BC) and endometrial cancer (EC) is not well established in women with metachronous primary tumors. We sought to examine this interval and identify associations with treatment-related and clinicopathologic factors. Methods: We identified 141 patients who developed both cancers during 1966 to 2013. Patients were divided into 2 groups: group 1, BC first, and group 2, EC first. Subanalysis performed of group 1 (59 patients) stratified around adjuvant tamoxifen use: pre-1990 BC diagnosis and post. Results: Fifty-nine and 82 patients were in groups 1 and 2, respectively. The mean time interval was comparable (76 vs 74 months, P = 0.861). Subanalysis divided group 1 into pre- (n = 27) and post- (n = 32) 1990 and resulted in different mean time intervals between diagnosis of metachronous cancers (106 vs 50 months, respectively [ P = 0.042]). Median progression-free survival (PFS) and overall survival (OS) for EC were longer in the pre group (PFS, 51 vs 26 months [ P = 0.169]; OS, 59 vs 27 months [ P = 0.190]). Median PFS and OS for BC were also longer in this group (PFS, 147 vs 109 months [ P = 0.005]; OS, 166 vs 114 months [ P < 0.001]). Conclusions: Our data indicate the mean time interval between the diagnosis of EC and BC was approximately 6 years. Disease-specific EC survival was worse for patients with a previous diagnosis of BC. Stratification around implementation of tamoxifen use shows comparable grade and stage but different time interval and survival, suggesting resulting effects from adjuvant therapy for BC. These results are useful in counseling women at risk.